Imagens não Cotidianas: Escola de Aprendizes Artífices de Campos- 1910/1942 - Gomes, Luiz Claudio Gonçalves (2004)
In the present study we attempt to contribute to the history of the Escola de Aprendizes Artifices de Campos through the use of photography mixed with the combination of complementary sources, such as verbal history and the periodic press. With this aim in mind, we propose the historic and semiotic analysis of images. The Campos School has shown itself, as the others, unable to keep the unfortunate youngsters who have been frequenting its professionalizing courses. The photographs have registered a school with pupils in precarious economic conditions, but at the same time, they have also disclosed the proper incompetence of the educational establishment which shows indexes below the national average, although the city has enjoyed relative political, geographical and economical privileges.